Genomic integrity in the male germ line: evidence in support of the disposable soma hypothesis. Issue 3 (September 2018) - Xavier, Miguel J; Mitchell, Lisa A; McEwan, Kristen E; Scott, Rodney J; Aitken, R John
Abstract : The Big Blue λ Select-cII selection system has been employed along with whole-exome sequencing to examine the susceptibility of the male germ line to mutation in two challenging situations (i) exposure to a chemotherapeutic regime including bleomycin, etoposide and cis -platinum (BEP) and (ii) the ageing process. A 3-week exposure to BEP induced complete azoospermia associated with a loss of developing germ cells and extensive vacuolization of Sertoli cell cytoplasm. Following cessation of treatment, spermatozoa first appeared in the caput epididymis after 6 weeks and by 12 weeks motile spermatozoa could be recovered from the cauda, although the count ( P  < 0.001) and motility ( P  < 0.01) of these cells were significantly reduced and superoxide generation was significantly elevated ( P  < 0.001). Despite this increase in free radical generation, no evidence of chromatin instability was detected in these spermatozoa. Furthermore, embryos obtained from females mated at this 12-week time point showed no evidence of an increased mutational load. Similarly, progressive ageing of Big Blue mice had no impact on the quality of the spermatozoa, fertility or mutation frequency in the offspring despite a significant increase in the mutational load carried by somatic tissues such as the liver ( P  < 0.05). We conclude that the male germ line is highly resistant to mutation in keeping with the disposable soma hypothesis, which posits that genetic integrity in the germ cells will be maintained at the expense of the soma, in light of the former's sentinel position in safeguarding the stability of the genome.